2003
DOI: 10.1002/jemt.10411
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent changes in thymic macrophages and dendritic cells

Abstract: Aging is characterized by the decline and deregulation of several physiological systems, especially the immune system. The involution of the thymus gland has been identified as one of the key events that precedes the age-related decline in immune function. Whereas the decrease in thymocyte numbers and in the thymic output during thymus atrophy has been analyzed by various authors, very little information is available about the age-associated modifications in thymic macrophages and dendritic cells. Here we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 107 publications
1
34
0
2
Order By: Relevance
“…In the present study, we observe numerous thymic nurse cells in normal full-term newborn baboons in spite of physiologic cortical involution, similar to the persistence of thymic dendritic cells during normal thymic involution (52). Thus, the reduction in thymic nurse cells in 125-d/ PRN animals appears to be a pathologic condition, suggesting that thymic nurse cells do not survive during involution associated with injury, infection, or stress.…”
Section: Discussionmentioning
confidence: 69%
“…In the present study, we observe numerous thymic nurse cells in normal full-term newborn baboons in spite of physiologic cortical involution, similar to the persistence of thymic dendritic cells during normal thymic involution (52). Thus, the reduction in thymic nurse cells in 125-d/ PRN animals appears to be a pathologic condition, suggesting that thymic nurse cells do not survive during involution associated with injury, infection, or stress.…”
Section: Discussionmentioning
confidence: 69%
“…Zavala and Cavicchia (2006) observed changes in both morphology and expression (density) of CD1a on LCs in gingival epithelium from elderly subjects. Varas et al (2003) observed that thymic stromal DCs were only slightly affected by age. Increased inflammatory activity accompanies normal aging brain.…”
Section: Numbers Phenotype and Differentiationmentioning
confidence: 98%
“…However, while the Sirpa 1 cDC decrease in proportion in the spleen, they increase in proportion in the ageing thymus. Previous studies have not investigated the changes in DC subsets in the ageing mouse thymus, whereas in the ageing human thymus it has been reported that there is a decrease in total thymic DC numbers, 48,49 but no change in their relative proportion. 49 Although in these studies the different subsets of human thymic DC were not defined, in general they are consistent with the results from our studies, where the predominant DC population in the thymus, the CD8a 1 cDC, also decreases in numbers but not in proportion until after middle age.…”
Section: Discussionmentioning
confidence: 95%